2013
DOI: 10.1080/14330237.2013.10820615
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Wellness Among Employees Working in the Nursing Environment

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
3
15
0
6
Order By: Relevance
“…They found emotional intelligence has a negative contribution on emotional exhaustion. Similar associations between high emotional intelligence and burnout utilising the Schutte Emotional Intelligence Scale and the Maslach Burnout Inventory were found among South African nurses (Nel, Jonker & Rabie, 2013), secondary school teachers (Cohen and Abedallah, 2015), and primary school teachers (Platsidou, 2010).…”
Section: Emotional Intelligence and Work-related Psychological Healthsupporting
confidence: 59%
“…They found emotional intelligence has a negative contribution on emotional exhaustion. Similar associations between high emotional intelligence and burnout utilising the Schutte Emotional Intelligence Scale and the Maslach Burnout Inventory were found among South African nurses (Nel, Jonker & Rabie, 2013), secondary school teachers (Cohen and Abedallah, 2015), and primary school teachers (Platsidou, 2010).…”
Section: Emotional Intelligence and Work-related Psychological Healthsupporting
confidence: 59%
“…In addition, no previous study identified the correlates of EI and intent to stay among nurses working in Jordanian hospitals. Nel, Jonker, and Rabies (2013) suggest that poor EI is associated with difficulty in responding to job demands, burnout and reduced commitment. Also, Trivellas, Gerogiannis, and Svarna (2013) found that only self-emotion appraisal (SEA) and one's use of personal emotions (UOE) have a direct impact on nurses' intention to stay in their jobs.…”
mentioning
confidence: 99%
“…Garrosa, Moreno-Jiménez, Rodríguez-Muñoz & Rodríguez-Carvajal [36] found that personal resources, such as emotional competence, were closely related to engagement in nursing, whereas a study of nurses' perceptions about the skills they need to do their jobs successfully showed social intelligence to be a predictor of engagement [11]. Nel, Jonker & Rabie [37] suggested that people who were not emotionally intelligent would not be able to deal with the demands of their jobs and would be more likely to succumb to burnout and reduced commitment, which would end up affecting their wellbeing at work.…”
Section: Introductionmentioning
confidence: 99%